2022
DOI: 10.1038/s41598-022-13001-x
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis to explore the biological association between environmental skin diseases and ambient particulate matter

Abstract: Although numerous experimental studies have suggested a significant association between ambient particulate matter (PM) and respiratory damage, the etiological relationship between ambient PM and environmental skin diseases is not clearly understood. Here, we aimed to explore the association between PM and skin diseases through biological big data analysis. Differential gene expression profiles associated with PM and environmental skin diseases were retrieved from public genome databases. The co-expression amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…Air pollution may be related to the development and exacerbation of AD [ 30 , 31 , 32 , 33 ]. Woo et al [ 34 ] reported that PM 10 exposure induces and aggravates skin inflammation via the differential expression of genes controlling skin barrier integrity and immune response in ovalbumin (OVA)-treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…Air pollution may be related to the development and exacerbation of AD [ 30 , 31 , 32 , 33 ]. Woo et al [ 34 ] reported that PM 10 exposure induces and aggravates skin inflammation via the differential expression of genes controlling skin barrier integrity and immune response in ovalbumin (OVA)-treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…Particulate matter emissions caused by the transportation sector remain of particular concern for the environment and human health, especially in urban areas [1,2]. Several toxicological and epidemiological studies reveal a correlation between traffic pollutants and adverse health effects such as an increased risk for lung cancer, coronary atherosclerosis, and skin diseases [3][4][5][6]. Particulate emissions from road traffic consist of exhaust particles, generated by incomplete combustion of fuels or by evaporation of lubricating oil components, and non-exhaust particles, which are either generated by the vehicles or already exist in the environment and are stirred up by the vehicles and resuspended into the air [7].…”
Section: Introductionmentioning
confidence: 99%